The Feynman-like procedure of ordered exponential operators applied to solar neutrinos - Bellandi, J.; Guzzo, M. M. (Elsevier, 1993)
An analytic resonant solution to the solar neutrino problem induced by small solar magnetic field phase velocity is derived using the Feynman-like procedure of ordered exponential operators. We assume the standard solar model matter distribution inside the Sun and the model proposed by Akhmedov and Bychuk for the solar magnetic field to conclude that a neutrino magnetic moment of order (5-8)×10-13μB is sufficient to explain the experimentally observed solar neutrino deficit, an improvement by a factor (2-4) relative to the conventional resonant spin-precession solution induced by neutrino squared mass difference when the same solar characteristics are considered. © 1993.